Pengaruh Employee Stock Ownership Program, Leverage, Ukuran Perusahaan, GCG, Nilai Tukar Dan Pajak Tangguhan Terhadap Kinerja Keuangan Pada Perusahaan Properti Dan Real Estate Yang Listing Di BEI Periode 2016-2020 - Steffani Steffani; Stella Stella; Trimawati Lumbantobing; Yentika Tanti; Bayu Wulandari; Mhd Zulkifli Hasibuan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was conducted to analyze the effect of the ESOP Employee Stock Ownership Program, Leverage, Company Size, GCG, Exchange Rates and Deferred Taxes on the Financial Performance of Property and Real Estate Companies Listing on the IDX for the 2016-2020 period. Quantitative approach is the method of this research. The research population totaled 65 Property and Real Estate Companies listed on the IDX for the 2016-2020 period. Using purposive sampling for sampling, the sample in the study amounted to 9 companies. The results show that research on ESOP, Leverage, Company Size, GCG, Exchange Rates and Deferred Taxes have an effect on the Financial Performance of Property and Real Estate Companies Listing on the IDX for the 2016-2020 period. Partial test results show that the Employee Stock Ownership Program (ESOP) has an effect on the financial performance of property and real estate companies listed on the IDX for the 2016-2020 period. Partial test results show that leverage has no effect on financial performance in property and real estate companies listed on the IDX for the 2016-2020 period. Partial test results show that company size has an effect on financial performance in property and real estate companies listed on the IDX for the 2016-2020 period. Partial test results show that GCG has no effect on the financial performance of property and real estate companies listed on the IDX for the 2016-2020 period. Partial test results show that exchange rates have no effect on financial performance in property and real estate companies listed on the IDX for the 2016-2020 period. The results of the partial test show that Deferred Tax has no effect on the Financial Performance of Property and Real Estate Companies Listing on the IDX for the 2016-2020 period. Keywords: ESOP, Leverage, Company Size, GCG, Exchange Rate, Deferred Tax